2006
DOI: 10.1111/j.1532-5415.2006.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of In‐Home Rehabilitation on Task Self‐Efficacy in Mobility‐Impaired Adults: A Randomized Clinical Trial

Abstract: A multifactorial, individualized, home-based OT/PT intervention can improve self-efficacy in mobility-impaired adults. The trend toward increased self-efficacy irrespective of the mode of rehabilitation delivery suggests that telerehabilitation can be a viable alternative to or can augment traditional in-home therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 38 publications
2
58
0
3
Order By: Relevance
“…This finding is consistent with other rehabilitation research that has similarly demonstrated the effectiveness of confidence-enhancing interventions among various populations. [35][36][37] Our results are unique, however, in that the evidence is specific to confidence with using a wheelchair.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This finding is consistent with other rehabilitation research that has similarly demonstrated the effectiveness of confidence-enhancing interventions among various populations. [35][36][37] Our results are unique, however, in that the evidence is specific to confidence with using a wheelchair.…”
Section: Discussionmentioning
confidence: 68%
“…This finding is consistent with other rehabilitation research that has similarly demonstrated the effectiveness of confidence-enhancing interventions among various populations. [35][36][37] Our results are unique, however, in that the evidence is specific to confidence with using a wheelchair.Although the results of the primary analysis support the use of the WSTP to improve overall confidence with using a wheelchair, secondary analyses revealed the intervention to be more effective at improving confidence in specific areas. For example, differences between the groups' mean change scores were found to be most significant in the area related to maneuvering the wheelchair in the physical environment.…”
mentioning
confidence: 68%
“…15 This study included 82 individuals adjusting to new mobility devices (i.e. wheelchair or walker) in the community.…”
mentioning
confidence: 99%
“…The study reported that potential use of televideo sessions was encouraging for meeting the needs of in-home PTs/OTs [15]. In a study on remote assessment of low back pain, Truter et al also addressed the practicality of TR, in particular by PTs in rural clinical settings.…”
Section: Literature Reviewmentioning
confidence: 99%